Giving Voice: Examining the Tactical Repertoires of Nonprofit Advocacy for Disadvantaged Populations - MacIndoe Heather; Beaton Erynn E.; Manuella Pache de Athayde Maria; Ojelabi Olanike (Nonprofit Policy Forum)
Representation is an important role of the nonprofit sector as these organizations can give voice to the priorities of their constituents. This is particularly important for disadvantaged communities that may lack access to traditional democratic processes. What advocacy tactics are most utilized by nonprofit organizations serving disadvantaged populations? Given variation in nonprofit advocacy tactics, which tactics are perceived as most effective? To answer these questions, we look to the framework of tactical repertoires from sociological studies of social movements. Analysis of a survey of New England nonprofits (N = 656, 55 % response rate) indicates that nonprofits serving disadvantaged populations use similar tactics to organizations advocating for other constituencies but employ them at higher rates. These tactics cluster into three tactical repertoires, each a different combination of advocacy tactics. Perceptions of advocacy effectiveness are associated with the size and nature of tactical repertoires, client participation in advocacy, government funding, and perceptions of the policy environment.